STRATEGI PEMASARAN INDUSTRI CAFÉ DI SENTRA PARIWISATA PANTAI KEDONGANAN UNTUK MENGATASI KRISIS EKONOMI GLOBAL - I P. Sudana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2010)
The existence of cafe industry in Kedonganan beach as a component of new tourism products must be consistently preserved. For its sustainability, all marketing problem should be well overcome for the customer’s satisfaction. Based on Internal-External matric analysis, the position of cafe industry in Kedonganan beach tourism centre are in cell I, it means that the cafe industry must apply the strategies of grow and build consisting of market penetration, market development, and product development strategies.